Unveiling and blocking the interaction between tomato spotted wilt virus and its insect vector, Frankliniella occidentalis - Montero Astúa, Mauricio (Kansas State University, 2014)
Tomato spotted wilt virus (TSWV) is an economically important plant virus dependent on insects (thrips) for transmission to plant hosts. Like many animal-infecting viruses, TSWV replicates in the cells of its insect vector. The virus is an emergent disease threatening food and fiber crops worldwide. The aim of this work was to develop novel control strategies against TSWV through a better understanding of the virus-vector interaction. Previously, the TSWV GN protein was shown to be the viral attachment protein, a molecule mediating attachment of virus particles to the midgut epithelial cells of vector thrips. The specific goals of my research were to further examine the utility of disrupting the virus-vector interaction for effective virus control by exploiting GN properties, and to track the route of TSWV in thrips using confocal microscopy. To achieve these goals, I expressed soluble and insoluble forms of GN fused to green fluorescent protein (GFP) transiently and transgenically and examined their cellular localization in planta. GN:GFP recombinant protein localized to Golgi stacks throughout the cells as indicated by a punctate pattern or co-localization to a Golgi marker. In contrast, the soluble form of GN, GN-S:GFP, localized to the ER and apparently also to the cytoplasm. Virus acquisition and transmission assays with GN-S:GFP transgenic tomato plants demonstrated that transmission of TSWV by F. occidentalis was reduced by 35 to 100%. These results indicated that transgenic expression of GN-S in tomato plants may have the potential to prevent secondary spread of the virus. Novel features of the morphology of principal (PSGs) and tubular salivary glands (TSGs) of the insect vector F. occidentalis and of their infection with TSWV were described. The virus colonized different cell types and regions within the PSGs with variable intensity and distribution; and accumulated at the lumen of individual cells. The TSGs of F. occidentalis are proposed as a route for TSWV infection into the PSGs. The transgenic plants and the new knowledge of the virus vector interaction are promising tools to control TSWV and a model approach for the control of other vector-borne viruses.
Keywords: Plant virus-vector interaction; Bunyaviridae; Transmission-blocking technology; Transgenic tomato; Salivary glands; Dynamics of infection; Entomology (0353); Plant Pathology (0480); Virology (0720)